2015
DOI: 10.1016/j.apcatb.2014.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Fe/SSZ-13 as an NH3-SCR catalyst: A reaction kinetics and FTIR/Mössbauer spectroscopic study

Abstract: Using a traditional aqueous solution ion-exchange method under a protecting atmosphere of N 2 , an Fe/SSZ-13 catalyst active in NH 3-SCR was synthesized. Mössbauer and FTIR spectroscopies were used to probe the nature of the Fe sites. In the fresh sample, the majority of Fe species are extraframework cations. The likely monomeric and dimeric ferric ions in hydrated form are [Fe(OH) 2 ] + and [HO-Fe-O-Fe-OH] 2+ , based on Mössbauer measurements. During the harsh hydrothermal aging (HTA) applied in this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 47 publications
(84 reference statements)
6
123
0
1
Order By: Relevance
“…For potential practical applications, the authors suggested that Fe/SSZ-13 may be used as a cocatalyst together with Cu/CHA as integral aftertreatment SCR catalysts on the basis of the stable high temperature activity after hydrothermal aging. 37 Further, there exist a few studies in the literature addressing the hydrothermal synthesis of Fe/SAPO-34 catalysts, directly incorporating Fe into the structure, for the applications of chloromethane transformation to light olefins and of methanol conversion. 34,35 In a recent patent application, NH 3 SCR of Fe/SAPO-34, with Fe incorporated into the structure, was studied, but only up to 500 C.…”
Section: Usamentioning
confidence: 99%
See 1 more Smart Citation
“…For potential practical applications, the authors suggested that Fe/SSZ-13 may be used as a cocatalyst together with Cu/CHA as integral aftertreatment SCR catalysts on the basis of the stable high temperature activity after hydrothermal aging. 37 Further, there exist a few studies in the literature addressing the hydrothermal synthesis of Fe/SAPO-34 catalysts, directly incorporating Fe into the structure, for the applications of chloromethane transformation to light olefins and of methanol conversion. 34,35 In a recent patent application, NH 3 SCR of Fe/SAPO-34, with Fe incorporated into the structure, was studied, but only up to 500 C.…”
Section: Usamentioning
confidence: 99%
“…In a very recent work, an active Fe/SSZ-13 catalyst for NH 3 -SCR was successfully synthesized by traditional aqueous solution ion-exchange method under the protection of N 2 . 37 The method used in the study was applied to prevent Fe 2+ ions from being oxidized to bulky Fe 3+ moieties (e.g., FeO(OH)) that can hardly penetrate into zeolite pores. It was demonstrated that the small pore CHA structure does not impede Fe 2+ ion exchange and the formed Fe species become active at temperature above 400 o C after aging of the Fe/SSZ-13 catalyst.…”
Section: Usamentioning
confidence: 99%
“…Details about the chemicals used and the synthesis procedure can be found elsewhere. 25 The assynthesized material was calcined in air at 550 °C for SDA combustion to obtain fresh 4 Na/SSZ-13. This material was further ion-exchanged with a 0.1 M NH 4 NO 3 solution at 80 °C to form NH 4 /SSZ-13; again detailed procedures can be found elsewhere.…”
Section: Catalyst Synthesismentioning
confidence: 99%
“…Fe-containing catalysts, such as Fe/SSZ-13, are active for the NH 3 -SCR of NO x [5,6]. Recently, Fe-Ti spinel has been developed as an environmentally benign SCR catalyst, which showed excellent activity and selectivity at 300-400°C [7].…”
Section: Introductionmentioning
confidence: 99%